Movements and Diving Behavior of the Eastern North Pacific Offshore Killer Whale (Orcinus orca) - Schorr, Gregory S.; Hanson, M. Bradley; Falcone, Erin A.; Emmons, Candice K.; Jarvis, Susan M.; Andrews, Russel D.; Keen, Eric M. (Frontiers in Marine Science, 2022)
The Pacific Offshore killer whale population is currently listed as data deficient on the IUCN Red List and Threatened in Canada. The population is estimated at 300 individuals with a range extending from Southern California to the Aleutian Islands in Alaska. Only 157 encounters with this ecotype have been photo-documented between 1988 and 2014; consequently, movement and behavioral data are limited and restricted to areas commonly surveyed. To better understand movements, habitat use, and diving behavior, we deployed seven dart-attached satellite tags during two encounters with Offshores off California and one encounter off Washington State in 2013. Group size estimates were 6, 9, and 30 whales, respectively. Transmission durations ranged from 6.3 to 147.4 days providing a combined 2,469 location estimates. Whales tagged in Southern California travelled from 30.7°N to 59.3°N degrees latitude, covering a larger latitudinal range in 75 days than all previous sightings (33.5°N to 60.0°N). Within most of the California Current (southern extent of locations up to 48.5°N), Offshores typically used waters deeper than the 200 m isobath. As they approached the northern extent of the California Current and travelled into British Columbia and Alaska, locations were more common near or inside the 200 m isobath. Individuals tagged in the same group disassociated and re-associated within the tracking duration, with animals tagged together separating by as much 1,339 km. Two of the tags also reported summarized diving behavior, and tags captured 1,110 total dives with median dive depths of 41 m and 100 m for each tagged whale; the maximum dive depth was 480 m. Dives were typically short (median = 3.9 and 4.1 min respectively, max = 12.3). A comparison of dive depths and bathymetry suggests that whales typically dove to or near the seafloor in continental shelf habitat. Despite the small number of tag deployments, these data provide new information on social structure, individual ranges, diving behavior, and habitat use of this seldom encountered killer whale ecotype.